Medical staff in Poland in 2012-2022 - challenges related to the distribution of human resources - Małyszko, Krystian; Pędziński, Bartosz; Maślach, Dominik; Krzyżak, Michalina; Marcinowicz, Ludmiła (Annals of Agricultural and Environmental Medicine, 2024)
Today's shortage of medical staff is a global healthcare issue. This leads to unfulfilled, growing health needs and rising wage pressure. The aim of the study is to evaluate employment trends among medical professionals in Poland from 2012-2022, paying particular attention to the employment sector, forms of employment, age, gender, and geographic distribution. A quantitative analysis was carried out using public records and documents to identify trends over a decade, by the desk research method. Sources included: Organisation for Economic Co-operation and Development databases, Central Statistical Office databases and Ministry of Health Statistical Bulletins. The observed increasing trend of physicians and nurses ratio after 2019, was caused mainly by a change in the methodology of calculating the indicator. There was a notable increase in the number of contracted medical professionals - 303% for nurses and 312% for midwives, and a decrease in the number of employed professionals. The number of contractors and employers in in-patient and long-term care has increased across all professional medical groups, while in outpatient care, the number has decreased. A definite ageing of medical staff was noted, with the percentage of midwives over 65 rising from 5.7% to 19.1%, and nurses over 65 rising from 5.4% to 22.3%. The demand for health services has increased, but the supply of medical staff has not kept pace with this demand. In addition to strategies related to increasing the number of human resources, solutions to better match resources to sectors of healthcare and better regional distribution should be considered. Solutions related to the skill-mix concept and the admission of new professions to the health sector may also be an opportunity for consideration.